為侵入性腦機介面技術進行倫理辯護: Ethical Defense of Invasive Brain-Computer Interface Technology - TANG, Jian (International Journal of Chinese & Comparative Philosophy of Medicine, 2023)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. The idea that invasive brain–computer interface technology is dangerous is debatable. This technology requires ethical justification, recognizing the coexistence of their benefits and risks. The newly formed professional consensus in China illustrates that it is possible to develop forward-looking and binding ethical guidelines through multidisciplinary argumentation and stakeholder consultation. Invasive brain–computer interfaces need not be limited to the smallest scope of application. Invasive brain–computer interfaces for healthy people and for enhancement purposes will provide technical and ethical options for future human society. Therefore, research into invasive brain–computer interfaces should not be prohibited. Rather, we must be alert to the risky possibility of research and development on brain–computer interfaces becoming entirely driven by business interests and controlled by capital. Furthermore, Chinese Taoist wisdom does not necessarily reject this technology.